Design of High‐Performance Disordered Half‐Heusler Thermoelectric Materials Using 18‐Electron Rule. (28th August 2019) - Liu, Zihang; Guo, Shuping; Wu, Yixuan; Mao, Jun; Zhu, Qing; Zhu, Hangtian; Pei, Yanzhong; Sui, Jiehe; Zhang, Yongsheng; Ren, Zhifeng
Abstract: Ternary half‐Heusler (HH) alloys display intriguing functionalities ranging from thermoelectric to magnetic and topological properties. For thermoelectric applications, stable HH alloys with a nominal valence electron count (VEC) of 18 per formula or defective HH alloys with a VEC of 17 or 19 are assumed to be promising candidates. Inspired by the pioneering efforts to design a TiFe0.5 Ni0.5 Sb double HH alloy by combining 17‐electron TiFeSb and 19‐electron TiNiSb HH alloys, both high‐performance n‐type and p‐type materials based on the same parent TiFe0.5 Ni0.5 Sb are developed. First‐principles calculation results demonstrate their beneficial band structure having a high band degeneracy that contributes to their large effective mass and thereby maintains their high Seebeck coefficient values. Due to the strong Fe/Ni disorder effect, TiFe0.5 Ni0.5 Sb exhibits a much lower lattice thermal conductivity than does TiCoSb, consistent with very recently reported results. Furthermore, tuning the ratio of Fe and Ni leads to achieving both p‐ and n‐types, and alloying Ti by Hf further enhances the thermoelectric performance significantly. A peak ZT of ≈1 and ≈0.7 at 973 K are achieved in the p‐type and n‐type based on the same parent, respectively, which are beneficial and promising for real applications. Abstract : A peak ZT of ≈1 and ≈0.7 at 973 K are achieved in the p‐type and n‐type compounds based on the same parent TiFe0.5 Ni0.5 Sb through tuning the Fe/Ni composition ratio and Hf alloying at the Ti site, respectively. First principle calculations demonstrate the semiconducting‐type characteristic, high band degeneracy, and also large total density of states mass for TiFe0.5 Ni0.5 Sb.